2015
DOI: 10.1007/s10162-015-0508-x
|View full text |Cite
|
Sign up to set email alerts
|

Increased Sensitivity to Noise-Induced Hearing Loss by Blockade of Endogenous PI3K/Akt Signaling

Abstract: The PI3K/Akt signaling pathway is involved in mediating survival of sensory hair cells. Here, we investigated the involvement of PI3K/Akt in noise-induced hearing loss in both temporary and permanent threshold shift noise models. The PI3K regulatory subunit p85α and phosphorylation of Akt on serine 473 (p-Akt S473) are downregulated in sensory hair cells, including both outer and inner hair cells, and supporting cells of the mouse organ of Corti 1 h after exposure to permanent-threshold-shift-inducing noise (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 30 publications
2
28
0
Order By: Relevance
“…Endogenous PI3K/Akt signaling is an intrinsic inner ear protective mechanism that plays an active role in maintaining hair cell (HC) viability throughout life. A decrease in PI3K signaling correlated with a reduction in HC survival capacity with age .…”
Section: Discussionmentioning
confidence: 99%
“…Endogenous PI3K/Akt signaling is an intrinsic inner ear protective mechanism that plays an active role in maintaining hair cell (HC) viability throughout life. A decrease in PI3K signaling correlated with a reduction in HC survival capacity with age .…”
Section: Discussionmentioning
confidence: 99%
“…Another well-recognized survival signaling pathway is mediated by phosphatidylinositol 3 kinase (PI3K), protein kinase c (PKC) and protein kinase B (also known as AKT), which can also be activated by growth factors. Chen et al (2015) found that blocking PI3K/AKT signaling increased sensitivity to NIHL in animals.…”
Section: Survival Signaling and The Negative Regulation Of Hc Damagementioning
confidence: 99%
“…In relation to the effect of the use of siRNA in the cochlear hair cells gene expression, Mukherjea et al [22][23][24] observed a silencing rate of 70% for the NADPH oxidase 3 (NOX3) gene after siRNA trans-tympanic injection. In addition, Chen et al [25] observed a decrease of 30% in the p85α gene expression in hair cells of animals previously submitted to siRNA intra-tympanic injection and after noise exposure. These data corroborated our results, since that the trans-tympanic injection performed in this study was able to reduce the Tnfα gene expression to 26.31%, with a silencing rate of 74.1% observed after noise exposure comparing the control.…”
Section: Discussionmentioning
confidence: 98%